Weltagrarbericht: Bericht zu Afrika südlich der Sahara (SSA) - Albrecht, Stephan (Hamburg University Press, 2012)
The International Assessment of Agricultural Knowledge, Science and Technology for Development (IAASTD), adopted in Johannesburg, South Africa in 2008, is the result of a unique cooperative effort by UN and other international organizations, 60 governments and more than 400 scientists from all over the world.A Global Report and five Regional Reports describe the main problems facing agriculture, food, the environment and human health today and show how the urgent need for a turnaround towards sustainable, environmentally and socially equitable development and food security for a growing world population can be achieved in practice.The Regional Report on Sub-Saharan Africa (SUB-Saharan Africa, SSA) deals with a region that has to contend with numerous problems, but at the same time has magnificent and wonderful people and natural resources. Also published in German by Hamburg University Press is the "Synthesebericht" der Weltagrarbericht.